2019
DOI: 10.18203/2320-6012.ijrms20192893
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of mammography breast imaging reporting and data system score and fine needle aspiration cytology in the evaluation of palpable breast lump

Abstract: Background: Breast lump is one of the commonest complaints with which patients present in breast clinics. As in most cases breast lump ultimately leads to a diagnosis of breast cancer, it is important for women with a breast lump to receive appropriate evaluation. So initial diagnostic approach such as utilization of rapid, inexpensive, presumptive and safe method is utmost important as such methods not only would benefit both patients and clinicians by prompting proper preoperative diagnosis and management bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…presentation in our study was painless and mobile breast lump(92%) which was comparable with other study by Ken Munene Nkonge et al [13] (96%). b) Cytomorphological findings  In present study, out of 100 cases, benign breast lesions (55%) were more common than malignant breast lesions (45%) which was comparable with other studies: by Arpita Pandia et al [10] 55.43% & 38% cases reported as a benign & malignant respectively, by Ramesh S. Waghmare et al [14] 56.25% & 31.50% cases reported as a benign & malignant respectively and by Anto J. Richie [7] . 57.5% & 42.5% cases reported as a benign & malignant respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…presentation in our study was painless and mobile breast lump(92%) which was comparable with other study by Ken Munene Nkonge et al [13] (96%). b) Cytomorphological findings  In present study, out of 100 cases, benign breast lesions (55%) were more common than malignant breast lesions (45%) which was comparable with other studies: by Arpita Pandia et al [10] 55.43% & 38% cases reported as a benign & malignant respectively, by Ramesh S. Waghmare et al [14] 56.25% & 31.50% cases reported as a benign & malignant respectively and by Anto J. Richie [7] . 57.5% & 42.5% cases reported as a benign & malignant respectively.…”
Section: Discussionsupporting
confidence: 92%
“…a) Clinical presentation: 1. Incidence of Age: In our study, Out of 100 cases, maximum number of cases (29%) were between 41 to 50 years of age group which was correlated with other study: by Arpita Pandia et al [10] maximum number of cases (28%) were between 40-50 years of age group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study maximum numbers of patients with benign diagnosis were in 31-40 years age and majority of malignant cases were in the 41-50. This finding was consistent with the [11] previous study done by Garg et al . In our present study, out of 80 cases, benign breast lesions (67.5%) were more common than malignant breast lesions (32.5%) which was comparable with other studies by Arpita [12] Pandia et al which reported 55.43% & 38% cases reported as a benign & malignant respectively. In a study by Ramesh S. [14] study by Anto J. Richie .…”
Section: Discussionsupporting
confidence: 91%